Neanderthal genomics and the evolution of modern humans - Noonan, James P.

(untitled) (Genome Research, 2010)
Humans possess unique physical and cognitive characteristics relative to other primates. Comparative analyses of the human and chimpanzee genomes are beginning to reveal sequence changes on the human lineage that may have contributed to the evolution of human traits. However, these studies cannot identify the genetic differences that distinguish modern humans from archaic human species. Here, I will discuss efforts to obtain genomic sequence from Neanderthal, the closest known relative of modern humans. Recent studies in this nascent field have focused on developing methods to recover nuclear DNA from Neanderthal remains. The success of these early studies has inspired a Neanderthal genome project, which promises to produce a reference Neanderthal genome sequence in the near future. Technical issues, such as the level of Neanderthal sequence coverage that can realistically be obtained from a single specimen and the presence of modern human contaminating sequences, reduce the detection of authentic human–Neanderthal sequence differences but may be remedied by methodological improvements. More critical for the utility of a Neanderthal genome sequence is the evolutionary relationship of humans and Neanderthals. Current evidence suggests that the modern human and Neanderthal lineages diverged before the emergence of contemporary humans. A fraction of biologically relevant human–chimpanzee sequence differences are thus likely to have arisen and become fixed exclusively on the modern human lineage. A reconstructed Neanderthal genome sequence could be integrated into human–primate genome comparisons to help reveal the evolutionary genetic events that produced modern humans.